Asymmetries of men and women in selecting partner - Başar, Ömer. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
People seek their love partner throughout their lives. As the internet grows rapidly, the traditional mate finding ways start to change. The new trend of finding a mate is to join the online dating services. We work on the dataset of an online dating system in Turkey which has more than 4 million registered users. We investigate the asymmetries of men and women in selecting partner. We find out that some criteria are more crucial. The correlation between some properties are also studied. It is found that educational level and salaries are highly correlated. Some men do not give up until he gets a message from the woman who impressed him up. We investigate whether the insisting is effective to get attention of women. We also investigate the effect of beauty for both men and women. If a man is handsome, not surprisingly, finding a mate is easier. It is found that login times according to the gender, educational level and salary are asymmetric. Men with lower educational level or lower salary prefer to login to the system after 8 pm. The physical distance is also an important factor when selecting partner. We showed that men prefer women who lives nearby.
Keywords: Online dating.; Man-woman relationships -- Computer network resources.